2022
DOI: 10.26803/ijlter.21.10.13
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Natural Science Lesson-Plans Integrating the Principles of Transformative Pedagogy

Abstract: This paper investigated how graduating Natural Science pre-service teachers were able to integrate the principles of Transformative Pedagogy in their lesson-plan designs. The study draws on the theoretical tenets of Transformative Pedagogy, a form of pedagogy that combines social constructivism and critical theory, in order to teach for equity and equality. The study was qualitative in nature; it and made use of a documentary analytical method to respond to the primary research question: how do graduating Natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…Several studies have confirmed this. One of them is maximizing the function of pedagogy that combines social constructivism and critical theory in learning (Botes & Barnett, 2022). In the PGSD Study Program, the effectiveness of the RPS, especially in science learning, can be observed from student learning achievements in science courses (Syazali & Umar, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have confirmed this. One of them is maximizing the function of pedagogy that combines social constructivism and critical theory in learning (Botes & Barnett, 2022). In the PGSD Study Program, the effectiveness of the RPS, especially in science learning, can be observed from student learning achievements in science courses (Syazali & Umar, 2022).…”
Section: Resultsmentioning
confidence: 99%